PHILOSOPHY OF EDUCATION, VALUES AND UTOPIA IN THE CRITICAL PEDAGOGY OF PAULO FREIRE - Sacadura, Carlos Bellino (European Scientific Journal, ESJ, 2014)
This paper deals with some main issues of Paulo Freire´s philosophy of education, namely his relation with the history of education, theology, pedagogy, politics and science, and his perspectives of modernity and post-modernity. The framework of this study is the dialogue between pedagogy and philosophy, opening educational thought and practice to new humanistic and critical approaches. Another issue is the role of ethical values in education, and their relevance in a techno-scientific age.